EVALUASI MEKANISME PENGAWASAN MAHKAMAH KONSTITUSI TERHADAP KEKUASAAN KEHAKIMAN: TINJAUAN DARI PERSPEKTIF HUKUM TATA NEGARA - Alya Dwi Ananta; Luthfia Putri Pramesti; Nayla Marwa Nur Faizah; Muhammad Dzulfikar Ibnu Faza (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Abstrak. In a country that adheres to the rule of law, the principle of separation of powers characterizes the constitution, where state power is not centralized in one hand. Independent judicial power and the guarantee of human rights are an integral part of the legal system. The Constitution is the basic law that underlies the entire legal system, so “upholding law and justice” means upholding these three principles in the life of the state. The effectiveness of law enforcement is strongly influenced by the mechanism and work of the organization, the legal mechanism, and the judicial mechanism. In addition, the political will of decision-makers is also a factor that determines whether the law is upheld or not. Efforts to uphold the constitution and protect the rights of citizens characterize the ideals of the rule of law. Keywords: Judicial Power, Law Enforcement, Constitution, Legal Mechanism Abstrak. Dalam suatu negara yang menganut paham negara hukum, prinsip pemisahan kekuasaan menjadi ciri khas konstitusi, di mana kekuasaan negara tidak terpusat di satu tangan. Kekuasaan kehakiman yang merdeka serta jaminan hak-hak asasi manusia menjadi bagian integral dari sistem hukum. Konstitusi sebagai hukum dasar yang melandasi keseluruhan sistem hukum, maka